Thermal expansion, heat capacity and Grüneisen parameter of iridium phosphide Ir2P from quasi-harmonic Debye model. (March 2017) - Liu, Z.J.; Song, T.; Sun, X.W.; Ma, Q.; Wang, T.; Guo, Y.
Abstract: Thermal expansion coefficient, heat capacity, and Grüneisen parameter of iridium phosphide Ir2 P are reported by means of quasi-harmonic Debye model for the first time in the current study. This model combines with first-principles calculations within generalized gradient approximation using pseudopotentials and a plane-wave basis in the framework of density functional theory, and it takes into account the phononic effects within the quasi-harmonic approximation. The Debye temperature as a function of volume, the Grüneisen parameter, thermal expansion coefficient, constant-volume and constant-pressure heat capacities, and entropy on the temperature T are also successfully obtained. All the thermodynamic properties of Ir2 P in the whole pressure range from 0 to 100 GPa and temperature range from 0 to 3000 K are summarized and discussed in detail. Highlights: Some thermodynamic properties of cubic Ir2 P up to 3000 K are successfully obtained. First-principles calculations combines with quasi-harmonic Debye model are used. The pressure up to 100 GPa for the whole research.